Exposure to aflatoxins and fumonisins and linear growth of children in rural Ethiopia: a longitudinal study. Issue 12 (1st August 2021) - Tessema, Masresha; De Groote, Hugo; Brouwer, Inge D; De Boevre, Marthe; Corominas, Arnau Vidal; Stoecker, Barbara J; Feskens, Edith JM; Belachew, Tefera; Karakitsou, Anastasia; Gunaratna, Nilupa S
Abstract: Objective: We hypothesise that exposure to aflatoxins and fumonisins, measured in serum, alters protein synthesis, reducing serum protein and insulin-like growth factor 1 (IGF-1), increasing inflammation and infection, leading to child's linear growth failure. Design: Children 6–35 months, stratified by baseline stunting, were subsampled from an intervention trial on quality protein maize consumption and evaluated at two time-points. Setting: Blood samples and anthropometric data were collected in the pre-harvest (August–September 2015) and post-harvest (February 2016) seasons in rural Ethiopia. Participants: 102 children (50 stunted and 52 non-stunted). Results: Proportions of children exposed to aflatoxin G1, aflatoxin G2 and aflatoxin M1 were higher in the pre-harvest (8, 33 and 7, respectively) compared to post-harvest season (4, 28 and 4, respectively). The proportion of children exposed to any aflatoxin was higher in the pre-harvest than post-harvest season (51 % v . 41 %). Fumonisin exposure ranged from 0 % to 11 %. In joint statistical tests, aflatoxin exposure was associated with serum biomarkers of inflammation (C-reactive protein, α -1-glycoprotein) and protein status (transthyretin, lysine, tryptophan), IGF-1 and linear growth (all P < 0·01). However, exposure to specific aflatoxins was not significantly associated with any biomarkers or outcomes (all P > 0·05). Conclusions: Aflatoxin exposure among rural Ethiopian children was high, with large variation between seasons and individual aflatoxins. Fumonisin exposure was low. There was no clear association between aflatoxin exposure and protein status, inflammation or linear growth. A larger study may be needed to examine the potential biological interactions, and the assessment of aflatoxins in food is needed to determine sources of high exposure.